2020
DOI: 10.18549/pharmpract.2020.1.1696
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic observation study of medication counseling practices at retail chain pharmacies

Abstract: Objective: This study evaluated medication counseling procedures and trends at retail pharmacies in the Houston metropolitan area through a naturalistic observational study. Methods: A blinded cross-sectional observational study was conducted at retail pharmacies in the Houston metropolitan area. Data were collected by trained observers utilizing an observational log, to record various parameters that could have an impact on the duration of patient-pharmacist interaction in a naturalistic pharmacy practice set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[11][12][13][14] Despite the importance of medication counselling for patients, it has been shown to be sub optimally carried out by dispensing staff in studies from all over the world, and identified as an area requiring improvement. [15][16][17][18][19] However, a systematic review of interventions aimed at improving patient counselling conducted by Al Aqeel et al, found that only a few of the studies included in their review used theoretical frameworks to identify or design their interventions. 20 The frameworks used to design the interventions in these studies included the stages of change model, social cognitive theory, principles of motivational interviewing and the health belief model.…”
Section: Original Researchmentioning
confidence: 99%
“…[11][12][13][14] Despite the importance of medication counselling for patients, it has been shown to be sub optimally carried out by dispensing staff in studies from all over the world, and identified as an area requiring improvement. [15][16][17][18][19] However, a systematic review of interventions aimed at improving patient counselling conducted by Al Aqeel et al, found that only a few of the studies included in their review used theoretical frameworks to identify or design their interventions. 20 The frameworks used to design the interventions in these studies included the stages of change model, social cognitive theory, principles of motivational interviewing and the health belief model.…”
Section: Original Researchmentioning
confidence: 99%